Synthesis and Spectroscopic Properties of2-[1-Benzyl-1,2,3,-Triazolo-4]-5-Aryl-1,3,4-Oxadiazoles - Tashtuosh, Hasan; Abu-Orabi, Sultan; Ta'an, Eman; Al-Talab, Mahmoud (Asian Journal of Chemistry, 2010)
A series of 2-[1-benzyl-1,2,3-triazolo-4]-5-aryl-1,3,4-oxadiazoles 5a-1 were prepared via phosphorus oxychloride promoted dehydration of the corresponding carbohydrazides, 4a-1. The products were fully identified by NMR, IR, UV and MS spectroscopy and elemental analysis.